Climate change and the girl body: hope and the dystopian future in three novels by Monica Hughes - Thompson, William (My University, 2025)
Climate change fiction is one of the fastest growing genres for children and young adults in the twenty-first century. Young activists such as Greta Thunberg have provided a voice for children and young adults in response to climate change, reframing the conversation both politically and economically, particularly for those young people who will inherit the environmental damage of the last three centuries. Climate fiction, or cli-fi, as coined by journalist Dan Bloom in 2007 (Crace), has its roots in the fiction emerging from the environmental movement of the twentieth century. For children and young adults, cli-fi has a more direct connection to the science fiction and dystopian literature of the late twentieth and early twenty-first centuries. Since 2000, cli-fi for young adults has found a fuller expression in novels such as The Carbon Diaries duology (2008, 2010) by Saci Lloyd and Pacifica (2018) by Kristen Simmons, which depict a world altered by climate change. The increasing popularity of such texts speaks to the growing awareness among young adults of the political and economic impact of environmental devastation on a planetary scale.
Keywords: climate change fiction; cli-fi; children and young adults; awareness